2015
DOI: 10.1115/1.4028995
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Crushing of All-Metallic Corrugated Panels Filled With Close-Celled Aluminum Foams

Abstract: Under quasi-static uniaxial compression, inserting aluminum foams into the interstices o f a metallic sandwich panel with corrugated core increased significantly both its peak crushing strength and energy absorption per unit mass. This beneficial effect diminished however if the foam relative density was relatively low or the compression velocity became sufficiently high. To provide insight into the varying role o f aluminum foam filler with increasing compression velocity, the crushing response and collapse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…By element assembling procedure, the global matrices of mass M, structural stiffness K, geometric stiffness K G , aerodynamic stiffness K a , aerodynamic damping C a and the global nodal force vector F T caused by thermal expansion are obtained according to Equations (17), (21), (26), (31) and (28). The total kinetic energy, potential energy and work done by external force are given in terms of the global nodal displacement vector d, as…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…By element assembling procedure, the global matrices of mass M, structural stiffness K, geometric stiffness K G , aerodynamic stiffness K a , aerodynamic damping C a and the global nodal force vector F T caused by thermal expansion are obtained according to Equations (17), (21), (26), (31) and (28). The total kinetic energy, potential energy and work done by external force are given in terms of the global nodal displacement vector d, as…”
Section: Governing Equationsmentioning
confidence: 99%
“…Zhang et al discovered the limited enhancement of filling foam in compressive strength and impact resistance due to the relatively weak and low-density foam material [14]. Yan et al [15,16] and Yu et al [17] utilized closed-cell aluminum foam instead of polymeric foam and demonstrated that foam filler effectively improved compressive and bending strength by stabilizing effects on the corrugated members against buckling. Han et al [18] revealed that filling foam contributed to both enhanced buckling resistance and additional mass, and subsequently assessed the structural efficiency through optimization study.…”
mentioning
confidence: 99%
“…A constant velocity V was imposed on the front face sheet so that the core was uniaxially compressed. Much more modeling details can be seen in our previous study [8,46].…”
Section: Numerical Investigationmentioning
confidence: 99%
“…To improve the mechanical performance of a porous core, like its load-bearing capacity and impact resistance, researchers have assessed, experimentally and analytically, several approaches. These can be classified as follows: (1) improving the inherent properties of the core by changing its configuration 5,6 or by using a graded design for the parent materials of the core [7][8] or (2) adding a stiffener, like a thin-walled metal grid [9][10] or a tubular stiffener. [11][12] Experimental results show that the load-bearing capacity and energy absorption of a hybrid core composed of a foam core and a thin-walled grid significantly exceed the sum of the two separate components.…”
Section: Introductionmentioning
confidence: 99%